PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN EFEKTIVITAS KEMANFAATANNYA UNTUK MASYARAKAT SEKITAR INDUSTRI DI KOTA CILEGON - Andjar Astuti; Windu Mulyasari (Tirtayasa Ekonomika, 2016)
Issues of corporate social responsibility is an issue many researchers. it is because the issue of implementation and benefits of CSR is still widely questioned for the company and for the public. This study aimed to observe CSR issues. Companies that implement CSR still has problems to the external community. This research is expected to develop model solutions to solve problems in the implementation of CSR. CSR research conducted in industrial areas and communities in Cilegon Banten.Keyword: Corporate social responsibility